Acidity and specific gravity of goat milk produced by a group of breeders from the Costa Rican Central Plateau. - Chacón Villalobos, Alejandro (Agronomía Mesoamericana, 2004)
The evaluation was conducted at the Alfredo Volio Experimental Station of the University of Costa Rica and at the Dairy Processing Facility of the Costa Rican Association of Goat Breeders (A.C.C.C) both located in Ochomogo, Cartago. Goat milk supplied by the seven producers was evaluated from June 1st to December 31th of 2002. Weight, acidity expressed as Dornic units, and specific gravity of the milk brought to the facility by every producer were measured daily. From the total data that was gathered, a characteristic value of 17,7 ± 0,3 ºD for acidity and 1,029 ± 0,002 for specific gravity were determinated, both for a confidence level of 99%. ANOVA statistical essays were conducted followed by Scheffé post hoc test in order to study the variation of acidity and specific gravity at different months for all the data regardless of the producer. In the other hand variations on both parameters for each producer and among them over the moths were also studied by the statistical methodology mentioned above. The results obtained showed no significant differences in acidity for any of the evaluations (P≤0,05), however significant variations were detected for specific gravity for the same set of tests. When correlated, specific gravity and acidity showed a very low correlation coefficient of 0,03 which makes impossible to argue any sort of relation between both variables. The same happened when the weight of milk brought by every producer day by day was correlated with specific gravity (r = -0,67)